Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Grup Investigasi Terhadap Aktivitas dan Hasil Belajar Siswa Kelas X SMA Negeri 1 Bajeng Pada Konsep Ekosistem - Firdaus, Daud; Nunu Dwi, Warti (Fakultas MIPA UNM, 2011)
This quasy-experimental research aims to discover The Effect of Aplication of cooperative learning models Group Investigation (GI) type in regards to activity and result of the students’ studying at SMA Negeri 1 Bajeng at ecosystem concept. The research hypothesis is that the aplication of cooperative learning model Group Investigation (GI) type gives sicnificant effect to the activity and result of the students’ studying in class X SMAN 1 Bajeng at ecosystem concept. The sample in this research is the students of class X5 at SMA negeri 1 Bajeng as experimental class that included 33 students and the students of class X1 as control class that included 33 students. This research is conducted during 4 meetings. The result of descriptive statistic analysis shows that the average score of experiment class is 77,87 and control class is 70,98. The average score of the experimental class in learning activity is 64,24 and control class is 54,31. The result of inferential analysis techniques for the result of learning shows sig (2-tailed) 0,00 < α (0,05), and for learning activity show sig (2-tailed) 0,26 < α (0,05), then H0 is rejected and H1 is received. The result of correlation analysis techniques in the experimental class is 0,754 and cotrol class is 0,628, then there were the tight correlation between the result of learning and learning activity. From the research result, it can be concluded that there were the Effect of aplication cooperative learning models Group Investigation (GI) type in regards to acvtivity and result of students’ studying, and there were tight correlation between the result of students’ studing and learning activity of students at SMA Negeri 1 Bajeng at ecosystem concept.